Changes in force production after applying PNF...Coimbra Health School Annual Meeting, June 17-19, 2021. - Ferreira, Vitor Ferreira Vitor (European Journal of Public Health)
Background The performance of the vertical jump can benefit from techniques that enhance muscle strength. The application of certain PNF techniques can improve muscle activation and consequently the production of strength. The objective of this study was to understand the immediate changes produced by the application of the PNF Slow Reversal technique in the performance of the vertical jump. Methods An analytic, quasi-experimental and crossover study was designed. The data were collected in two sessions with at least 48 hours between them. In each session, three countermovement jumps were collected before and after the experimental and control protocol in a randomized order. The experimental protocol consisted of two diagonals of Slow Reversal technique with 15 repetitions of each. The control protocol consisted of 5 minutes of sitting (approximately the same time as the experimental protocol). The data were collected on a force platform and processed using an algorithm in MATLAB R2016b software. Results 18 female (mean age 20.7 ± 2.7 years, mean body mass of 71.6 ± 11.5 kg, mean height of 1.75 ± 0.07 m) athletes of amateur sports participated in the study. Some values with statistical significance were found. Particularly a decrease in the average force production in the concentric phase after the application of PNF (P = 0.024). Conclusions The application of PNF seems to induce acute effects in the production of force, in the performance of the vertical jump. The application of PNF may induce muscle adaptations that need to be better studied in the long term.